2016
DOI: 10.1093/bja/aew052
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is believing: getting the best out of videolaryngoscopy

Abstract: Complications secondary to airway management in anaesthesia are relatively rare but when they do occur, the causal and contributory factors are often attributed to human error related to inadequate training and poor judgement by the anaesthetist. 1 These complications continue to occur despite competencybased medical education curricula and detailed practice guidelines. One criticism of competency-based medical education is that it applies primarily to trainees and focuses too much on the Editorials | i13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 50 publications
2
106
0
1
Order By: Relevance
“…The benefits of VL are most significant in patients with difficult airways, as it converts "blind" intubations into intubations under visual control (9). In patients with difficult airways, VL can provide a higher intubation success rate and a shorter intubation time than DL (10)(11)(12).…”
Section: What Is Efficacy Of Videolaryngoscopy?mentioning
confidence: 99%
See 4 more Smart Citations
“…The benefits of VL are most significant in patients with difficult airways, as it converts "blind" intubations into intubations under visual control (9). In patients with difficult airways, VL can provide a higher intubation success rate and a shorter intubation time than DL (10)(11)(12).…”
Section: What Is Efficacy Of Videolaryngoscopy?mentioning
confidence: 99%
“…In fact, success with the application of any device is probable to be increased as experience is accumulated. If VL is used for all patients, experience and skill would undoubtedly increase, thus, number of intubation attempts and complications of multiple attempts would decrease, and patient care would improve (10). It has been suggested that the optimal VLs should be offered to all patients without significant limitations and not only in those considered most difficult (12).…”
Section: Should Videolaryngoscopy Be Used For All Intubations?mentioning
confidence: 99%
See 3 more Smart Citations